2008
DOI: 10.1007/s00432-008-0395-1
|View full text |Cite
|
Sign up to set email alerts
|

Expression and prognosis role of indoleamine 2,3-dioxygenase in hepatocellular carcinoma

Abstract: Our data indicated that IDO may be a novel favorable prognostic indicator and candidate adjuvant therapeutic target for HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
106
3
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(128 citation statements)
references
References 30 publications
10
106
3
1
Order By: Relevance
“…immune cells in the tumor microenvironment were also evaluated. Detection of immunosuppressive markers including PD-L1, CTLA-4, and IDO has been reported for various tumor types [4,[15][16][17][18][19][20][21][22][23][24][25][26][27]. In our study, the positive expression of PD-L1, CTLA-4, and IDO was noted in 43.6, 65.8, and 47.7 % of the cases, respectively.…”
Section: Discussionsupporting
confidence: 59%
“…immune cells in the tumor microenvironment were also evaluated. Detection of immunosuppressive markers including PD-L1, CTLA-4, and IDO has been reported for various tumor types [4,[15][16][17][18][19][20][21][22][23][24][25][26][27]. In our study, the positive expression of PD-L1, CTLA-4, and IDO was noted in 43.6, 65.8, and 47.7 % of the cases, respectively.…”
Section: Discussionsupporting
confidence: 59%
“…On the one hand, frequency of hepatic metastasis has been found to be significantly increased in patients with colorectal cancer presenting high IDO expression in their tumor (14). Strong IDO expression in hepatocellular tumors has also been associated with the presence of distant metastases (25). In addition, metastases in TDLNs have been found preferentially in patients with endometrial tumors expressing IDO at a high level (26).…”
Section: Regulatory T-cell Infiltration Increasementioning
confidence: 99%
“…In 2 studies, IDO expression evaluated by immunohistochemistry (IHC) and enzymatic activity has been inversely correlated with progression-free survival (16,26,31). Also, IDO measurement by IHC in hepatocellular carcinoma samples from 138 patients has established that low IDO expression correlates with an improved overall survival (25). For patients with invasive cervical cancer treated with radical hysterectomy, it has been observed that focal and diffuse IDO expression in cancer tissue correlates with decreased overall and progression-free survival, whereas patients with no IDO expression in their tumor had a better survival (30).…”
Section: Association With Patient Survivalmentioning
confidence: 99%
“…As in DCs, monocytes, and macrophages, an inverse correlation has been found in many tumour types between IDO expression and the number of tumour infiltrating CD8+ T cells (Brandacher et al 2006, Inaba et al 2009, Ino et al 2008, and Uyttenhove et al 2003. Overexpression of IDO by malignant cells is an important cancer induced immune escape mechanism and has been associated with poor prognoses for survival (Brandacher et al 2006, Inaba et al 2009, Ino et al 2008, Risenberg et al 2007, Inaba et al 2010, and Pan et al 2008. This finding, however, has increased the potential of using IDO inhibitors, such as 1-MT, in cancer treatments.…”
Section: Ido and Immunosuppressionmentioning
confidence: 98%